Iran-United States Claims Tribunal reports. edited by Lee M. Caplan. - Caplan, Lee (Cambridge University Press, 2022)
The Iran-US. Claims Tribunal, concerned principally with the claims of US nationals against Iran, is the most important international claims tribunal to have sat in over half a century. Its jurisprudence is bound to make a uniquely important contribution to international law and, in particular, the law relating to aliens, treaty law, and international arbitral procedure. The 40th volume of the Iran-US Claims Tribunal Reports makes available to the public the Tribunal's most recent work, including an important award in a large dispute between Iran and the United States. This volume of the Reports is a critical contribution to the field of international arbitration that will inform and guide the practice of international arbitration practitioners from around the world.